1966
DOI: 10.1017/s0007485300056686
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of the swede midge, Contarinia nasturtii (Kieff.) (Diptera, Cecidomyiidae). I.—Life-history and influence of temperature and moisture on development

Abstract: The life-history of Contarinia nasturtii (Kieff.), a gall-forming pest of swedes, was investigated in northern England in 1958–60, particular attention being paid to the influence of temperature and moisture on development in the soil. Most of the observations were made under controlled conditions in the laboratory, although much of the material came from the field.The adults emerge from the soil, mate, and live 1–3 days. In laboratory conditions, each female developed about 95 eggs, laid in batches of 2–50 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 9 publications
1
63
0
Order By: Relevance
“…However, why extremes of soil moisture contents can effectively hamper C. nasturtii emergence is unclear. Readshaw (1966) reported that C. nasturtii larvae could remain quiescent (dormant) and construct spherical cocoons when entering dry sandy loam (8Ð15% moisture content) and peaty clay soil (Ϸ43% moisture content) until the soils were thoroughly wetted. However, after C. nasturtii larvae in plant material were placed on top of the dry soil in our study, we observed that C. nasturtii larvae could still enter the soil but wrapped themselves with dry soil particles and became immobilized, instead Days to Þrst Loamy Þne sand 11.4 Ϯ 0.4 aC 12.7 Ϯ 0.3 abBC 11 Ϯ 0.6 cdC 13.5 Ϯ 2.5 bcB 18.5 Ϯ 0.5 cA emergence of burrowing into the soil, and died on top of the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, why extremes of soil moisture contents can effectively hamper C. nasturtii emergence is unclear. Readshaw (1966) reported that C. nasturtii larvae could remain quiescent (dormant) and construct spherical cocoons when entering dry sandy loam (8Ð15% moisture content) and peaty clay soil (Ϸ43% moisture content) until the soils were thoroughly wetted. However, after C. nasturtii larvae in plant material were placed on top of the dry soil in our study, we observed that C. nasturtii larvae could still enter the soil but wrapped themselves with dry soil particles and became immobilized, instead Days to Þrst Loamy Þne sand 11.4 Ϯ 0.4 aC 12.7 Ϯ 0.3 abBC 11 Ϯ 0.6 cdC 13.5 Ϯ 2.5 bcB 18.5 Ϯ 0.5 cA emergence of burrowing into the soil, and died on top of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Thygesen (1966) studied the emergence of C. nasturtii in different soil types and found emergence was markedly earlier in light sandy soil than in heavy clay. In addition, Readshaw (1966) reported that soil moisture could affect C. nasturtii emergence and even cause dormancy after mature larvae were placed in soil with three to four different moisture levels. Readshaw (1968) suggested that it may be possible to achieve satisfactory control of C. nasturtii by simple cultural procedures, such as burying pupae too deeply in the soil to permit successful emergence.…”
mentioning
confidence: 99%
“…Changing the precipitation or RH% had a much larger effect on the location of the bioclimatic envelope than altering the temperature values. This is not surprising because C. nasturtii is known to be sensitive to soil moisture (Readshaw, 1966). While precipitation and RH% are roughly substitutable, temperature and precipitation (or RH%) have an almost additive effect on the distribution of C. nasturtii, with little interaction between the variables (see Fig.…”
Section: Climate Factors Affecting Distributionmentioning
confidence: 93%
“…It is a key factor in the termination of diapause (Readshaw, 1966) and thus, adult emergence. We confirmed this conclusion in 'Climate factors affecting distribution' (see Fig.…”
Section: Climate Factors Affecting Distributionmentioning
confidence: 99%
See 1 more Smart Citation